Fogging With Peracetic Acid in Schools and Kindergartens - Ewelina Kruszewska; Henryk Grześ; Piotr Czupryna; Sławomir Pancewicz; Monika Groth; Mulugeta Wondim; Anna Moniuszko-Malinowska (Frontiers Media S.A., 2021)
Disinfection is a key element in controlling infections. Fogging, also known as fumigation, is one of the most effective chemical disinfection methods. Peracetic acid (PAA) is a powerful oxidant with bactericidal and fungicidal properties. The aim of this study is to determine the type of bacteria and fungi present in educational institutions and whether disinfection by PAA fumigation in these institutions is also effective and useful, as demonstrated previously in healthcare centers. This study was carried out in five kindergartens and five primary schools in Bialystok, Poland. Three rooms have been selected in each of these educational institutions, and the disinfection was carried out in 30 rooms in total. Fogging with PAA was performed in selected rooms. Before and after disinfection, samples were collected from four surfaces: walls, tables, doors, and chair backs. Most frequently detected microorganisms in schools and kindergartens were Micrococcus luteus (M. luteus), Staphylococcus warneri (S. warneri), Paracoccus yeei (P. yeei), Staphylococcus hominis ssp. hominis (S. hominis), Kocuria rhizophila (K. rhizophila), Kocuria rosea (K. rosea). In addition, Staphylococcus haemolyticus (S. haemolyticus), Acinetobacter lwoffii (A. lwoffii), Kocuria kristinae (K. kristinae), Lactococcus lactis ssp. lactis (L. lactis) were the most prevalent in kindergartens, whereas Kytococcus sedentarius (K. sedentarius) was the most prevalent in schools. Comparison of the bacterial flora of schools and kindergartens showed statistically significant differences in the prevalence of bacteria on different surfaces. A significant decrease in the number of colonies after disinfection was observed on all surfaces (p < 0.05). In addition, the calculated effectiveness of disinfection was 99.7% in kindergartens and 99.3% in schools. The results indicate that fogging of PAA is a highly effective method of surface disinfection in kindergartens and schools.